Self-management preferences in patients with mild cognitive impairment: A qualitative study - Jiao, Yuchen; Liu, Chang; Chang, Jing; Zhou, Shiyu; Ji, Yan (Frontiers in Psychology, 2022)
Purpose: Patients with mild cognitive impairment (MCI) require self-management, yet current self-management compliance is low. Taking patients' preferences into account can improve the self-management situation. The purpose of this study is to look into MCI patients' preferences for self-management in China. Methods: A qualitative research was conducted using semi-structured in-depth interviews with 21 patients recently diagnosed with MCI who were chosen by purposive sampling. These interviews were analyzed through thematic analysis and identified emerging themes. Results: Five themes of self-management preference were identified: (1) Preference for acquiring disease knowledge; (2) Preference for participating in drug therapy; (3) Preference for participating in exercise; (4) Preference for applying memory compensation strategy; (5) Preferences for emotional expression and response. Conclusion: Our study identified the specific preferences of MCI patients in China for the main self-management items. The findings are valuable insights for knowing MCI patients' self-management content and preferences and provide better guidance for health practitioners to improve self-management compliance.